Tourist Attitudes Given the Quality of Promotion and Tourist Satisfaction in the Lontar Sewu Edutourism, Gresik Regency, Indonesia - Murtini, Sri; Sutedjo, Agus; Ibrahim, Mohd Hairy (The Journal of Society and Media, 2023)
The attitude of tourists can be shown by feeling happy, satisfied, and comfortable with what is enjoyed at the location of a tourist attraction. This will be demonstrated by behavior in the form of actions on the level of satisfaction, comfort, and pleasure obtained. This study aimed to determine the attitude of tourists in the Lontar Sewu ecotourism area, Hendrosari Village, Menganti, and Gresik Regency. The population is 50 tourists and tourism managers. Data collection techniques using interviews, questionnaires, and observations. Data analysis techniques using a Likert scale scoring. The results showed that the quality of the promotion obtained a score of 258 in the excellent category. Meanwhile, tourist satisfaction got a score of 309, or quite satisfied. With the quality of the advertising including good (score 3) and the joy of tourists being quite happy (2), the total score obtained is 5, then the attitude of tourists when they see the promotions being carried out and feel the situation in Lontar Sewu ecotourism is included in the category of quite happy (score 2)